Analisis Strategi Peningkatan Literasi Digital pada Pembelajaran Bahasa Indonesia - Evi Susanti; Indriyeni; Yuli Astuti (Perpustakaan Universitas Riau, 2024)
This study has three main objectives, namely (1) to evaluate the role of digital literacy in learning Indonesian in SMA Negeri 15 Pekanbaru, (2) to identify strategies to improve digital literacy in learning Indonesian in SMA Negeri 15 Pekanbaru, and (3) for Analyzing supporting factors and inhibiting the implementation of the strategy. The research method used is a qualitative approach with descriptive characteristics, using observation, interviews, and documentation as a method of data collection. The results of this study reveal that (1) the role of digital literacy in learning Indonesian involves improving the skills of utilizing digital media for in -depth learning, access to information from the internet, and the use of digital media as a communication tool in providing educational material. The teacher also applies the method of cultural movement to read diligently with a LIBERASI’s program to read books, write reviews, and share these activities through social media. (2) Digital literacy improvement strategies involve strengthening character through the use of digital media, reading books or electronic media, providing learning links, and the use of creative applications to increase creativity and motivation to learn Indonesian. (3) Supporting factors involve comprehensive support from schools by providing digital facilities and infrastructure, while inhibiting factors include limited data quota and internet network disorder during learning.